Strain-controlled Rashba spin-orbit coupling effect in SnS and SnSe monolayers. (1st November 2021) - Su, Jinhao; Wang, Xiting; Shao, Chen; Guo, Yuzheng; Xian, Lede
Graphical abstract: Highlights: Strains make the bandgaps of SnS and SnSe monolayers have an indirect-direct-zero transition. SnS and SnSe monolayers have a unidirectional Rashba spin–orbit coupling effect emerging at the asymmetric point. SnS and SnSe monolayers have a stronger Rashba spin splitting than InGaAs/InAlAs heterojunction and Au(1 1 1) surface. Strains can tune Rashba energy, momentum shift, and Rashba spin splitting strength of SnS and SnSe monolayers obviously. Abstract: The miniaturization of transistors and the high density of integrated circuits makes conventional transistors reach a size limit, causing leakage currents, unstable performance, and increasing production cost. Spin field effect transistors (SFETs) based on spintronics use electron spin as an information carrier and regulate electron spin degree of freedom for storing and processing information. As a class of spintronics, Rashba spin–orbit coupling (SOC) effect attracts increasing attention because of its electric tunability. SFETs based on Rashba SOC and two-dimensional materials will make a qualitative leap in future semiconductor devices. Based on first-principles calculations, it is found that the applied strains along zigzag (ZZ), armchair (AC), and biaxial direction make the bandgaps of SnS and SnSe monolayers (ML) have an indirect-direct-zero transition. SnS and SnSe ML have a more stable electron spin and stronger Rashba spin splitting than InGaAs/InAlAs heterojunction and Au(1 1 1) surface. For SnS ML, 6% tensile strain along ZZ direction not only stabilizes the electron spin but also strengthens Rashba spin splitting to a maximum of 0.76 eV Å. For SnSe ML, 2% tensile strain along biaxial direction makes Rashba spin splitting strength reach a maximum of 1.33 eV Å.